A geografia ensinada: mudanças e continuidades do conhecimento geográfico escolar (1960 1989) - Gomes, Daniel Mendes (2010)
This paper deals with the changes in the content of the geography subject in the period from 1960 to 1989. The objective is to contribute to the studies on History of School Subjects with the study of geography as a school subject, to point out the interruptions and continuities of the knowledge of this subject. In order to identify what is behind the changes and continuities of the content of geography, didactic works of the main authors from the abovementioned period will be analyzed. The textbook is the main source of this research since the analysis I propose is to verify the changes in the actual syllabus. Other research sources will also be consulted, such as the proposal and laws that organize the formal syllabus, the periodical publications of such subject o Boletim Paulista de Geografia [São Paulo Bulletin of Geography], the journal Orientação [Orientation] and the annals of meetings and congresses of geography made by AGB [Association of Brazilian Geographers]